2021
DOI: 10.1126/scisignal.abe4090
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of G protein signaling in Arabidopsis through two distinct pathways that internalize AtRGS1

Abstract: In animals, endocytosis of a seven-transmembrane GPCR is mediated by arrestins to propagate or arrest cytoplasmic G protein–mediated signaling, depending on the bias of the receptor or ligand, which determines how much one transduction pathway is used compared to another. In Arabidopsis thaliana, GPCRs are not required for G protein–coupled signaling because the heterotrimeric G protein complex spontaneously exchanges nucleotide. Instead, the seven-transmembrane protein AtRGS1 modulates G protein signaling thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 109 publications
0
13
0
Order By: Relevance
“…Moreover, a study in Arabidopsis showed that flg22 initiated AtRGS1 endocytosis through clathrin‐mediated endocytosis (CME), whereas Glc activated both CME and sterol‐dependent endocytosis. Flg22 and Glc induced endocytosis of AtRGS1 from separate plasma membrane origins and had different downstream signaling pathways (Watkins et al ., 2021), implying that the two pathways do not conflict and may coexist in the plant. It should be noted that some plants, like grasses, lack homologous RGS proteins (Urano et al ., 2012, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a study in Arabidopsis showed that flg22 initiated AtRGS1 endocytosis through clathrin‐mediated endocytosis (CME), whereas Glc activated both CME and sterol‐dependent endocytosis. Flg22 and Glc induced endocytosis of AtRGS1 from separate plasma membrane origins and had different downstream signaling pathways (Watkins et al ., 2021), implying that the two pathways do not conflict and may coexist in the plant. It should be noted that some plants, like grasses, lack homologous RGS proteins (Urano et al ., 2012, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Flg22 induces AtRGS1 internalization via clathrin-mediated endocytosis (CME), while D-glucose triggers both CME and sterol-dependent endocytosis (SDE). The recruitment of the CME endocytic machinery towards GPCRs requires prior β-arrestin binding and activation, but plant genomes do not encode these proteins [ 55 , 56 ]. Nevertheless, Arabidopsis has three proteins with arrestin folds that bind as heterodimers to AtRGS1 and are required for endocytosis [ 55 ].…”
Section: Phosphorylation and Internalization Of Rgs1 In An Arrestin-l...mentioning
confidence: 99%
“…The recruitment of the CME endocytic machinery towards GPCRs requires prior β-arrestin binding and activation, but plant genomes do not encode these proteins [ 55 , 56 ]. Nevertheless, Arabidopsis has three proteins with arrestin folds that bind as heterodimers to AtRGS1 and are required for endocytosis [ 55 ]. These include the vacuolar sorting proteins 26 (VPS26)—AtVPS26a, AtVPS26b, and AtVPS26-like components of the retromer [ 57 ], well-known in animals for their role in endosomal to plasma membrane anterograde trafficking [ 58 ].…”
Section: Phosphorylation and Internalization Of Rgs1 In An Arrestin-l...mentioning
confidence: 99%
See 2 more Smart Citations